A poética da natureza de Patativa do Assaré: uma abordagem ecocrítica - Rosa, Rosani Saleti da (2022)
Regarding environmental problems faced in our contemporaneity, socioenvironmentalists from all over the world mobilize with the objective of thinking about the relationship between human beings and nature. In view of this, systematic and interdisciplinary studies emerged in an attempt to question the utilitarian condition of natural goods as non-renewable resources. In this way, it was intended to broaden the discussions on Ecocriticism as an articulator of this interdisciplinarity. The concept of Ecocritical literary theory contributed to the analysis of our research. For this purpose, the objective of this research was to analyze the human-nature relationship in the poetics of Patativa do Assaré in an Ecocritical approach. For this, the following works were analyzed: Sing there, that I sing here (1978), Inspiração Nordestina (2003) and Ispinho e Fulô (2005), as such works focus on Literature and Ecology, based on the critical Ecocritical current. As results obtained from the analysis of the poems, it was possible to observe that the Patativian poetics was consolidated as a dual space: sertanejo space where rhymes bloom in the same rhythm that nature blooms; the sertão as a space of suffering and happiness; the apocalyptic space of the drought literature and, finally, a topophilic and biophilic literature in a new meaning of the subject-nature relationship. It was concluded that Ecocritique has become an important tool for analyzing the literary text, allowing for a reinterpretation of the human being-nature. In particular, the poetics of Patativa do Assaré allow us to look at place, being and existence in a uniqueness, in a triple inseparable aspect.